Downregulation by organic nitrogen of AOX1 promoter used for controlled expression of foreign genes in the yeast Pichia pastoris. Issue 5 (15th February 2019) - Velastegui, Edgar; Theron, Chrispian; Berrios, Julio; Fickers, Patrick
Abstract: Pichia pastoris is a well‐established cell factory for recombinant protein synthesis. Various optimization strategies of processes based on AOX1 promoter have been investigated, including methanol co‐feeding with glycerol or sorbitol during the induction stage. Compared with carbon sources, comparatively little research has been devoted to the effects of nitrogen sources. Several reports have described the benefits of adding casamino acids (CA) to the recombinant protein production medium, however, without considering its effects at the gene expression level. Using enhanced green fluorescent protein as a reporter protein, monitored using flow cytometry, CA was shown to downregulate AOX1 promoter induction. Despite higher growth rates, cultures containing CA exhibited slower transition to the induced state, whereas metabolite analysis revealed that methanol consumption was reduced in the presence of CA compared with its absence. The repressive effect of CA was further confirmed by analysing the synthesis of extracellular recombinant Candida antarctica lipase under control of the AOX1 promoter. These findings highlight nitrogen source selection as an important consideration for AOX1 ‐based protein production.